FUNGSI SUBSTITUSI SEBAGAI BENTUK PENGHILANGAN KEMONOTONAN DALAM NOVEL SURGA YANG TAK DIRINDUKAN 2 KARYA ASMA NADIA - Eki Youlanda; Erlina Zahar; Sujoko Sujoko (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
This purpose of this research is to describe the function of substituution to omit monotone in the novel Surga yang Tak Dirindukan 2 by Asma Nadia. Moreover, this research is also aimed at investigating literature which refers to research in language. This research is descriptive qualitative. The data is taken from quotes in a form of sentences in the novel Surga yang Tak Dirindukan 2 by Asma Nadia. The quotes which are related to the function of substitution in the novel are analyzed by using theory from Kridalaksana. The result of the research is there are 30 quotes which use the function of substitution in omitting monotone. This indicates that the writer of the novel uses the function of substitution to omit monotone so that readers of literature will not feel bored in reading the novel. From this research, it is suggested that the writers can serve literary works that can be enjoyed by the readers.Key Words: analysis, function of substitution, novel